AKIBAT HUKUM MUCIKARI DI BAWAH UMUR DENGAN MELIBATKAN ANAK DIBAWAH UMUR SEBAGAI KORBAN DALAM PROSTITUSI ONLINE - Wahyu Vidyaningsih; Habib Adjie (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
This increasingly rapid development of technology and information affects the acceleration in every field in the rotation of the activities of the wider community. But not only has a positive impact, but also has a negative impact. For example in the case of prostitution that is carried out online. In the news TribunJabar.Id reported the involvement of minors in online prostitution as operators and pimps. The emergence of legal problems related to the position of children involved in online prostitution cases as pimps is the background of this research with the aim of knowing the legal impact of online prostitution crimes committed by minors. The research will use a normative method with a statutory and bibliographical approach. It was concluded that the sanctions that can be imposed on minors who are involved in online prostitution are by taking action in accordance with Law number 11 of 2012 if they are under 15 years old, and a maximum of ½ (half) of the maximum criminal penalty if they are over 15 years old.